Method for preparing metal-organic framework material by degrading waste nylon 66
The synthesis of MOF in the presence of strong alkali compounds is solved by hydrothermal reaction and stirring, and the problems of efficient degradation of waste nylon 66 and high cost of MOF materials are achieved, and the preparation of high value-added MOF is achieved, which is suitable for a variety of application fields.
Patent Information
- Application Number
- CN202411226443.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-03
AI Technical Summary
The prior art is difficult to effectively degrade waste nylon 66, and the preparation method of existing MOF materials is high in cost and complicated in process. In particular, MOF using aliphatic carboxylate as ligand is difficult to synthesize in water.
Nylon 66 is hydrolyzed in the presence of a strong alkali compound to obtain a nylon 66 degradation solution, and then stirred and reacted with the metal salt solution at room temperature to synthesize MOF materials, controlling the temperature and time to achieve efficient degradation and synthesis.
The efficient degradation of waste nylon 66 into high-value-added MOF materials is achieved, which simplifies the process flow and reduces costs. The obtained MOF has unique breathing effect, gas adsorption selectivity and thermal stability, and is suitable for photochemical and environmental monitoring. field.
Smart Images

Figure CN119119496A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of waste polymer degradation and metal-organic framework (MOF) material preparation, and more specifically, relates to a method for preparing MOF material by degrading waste nylon 66, which provides a new low-cost strategy for the synthesis of MOF material. Background Art
[0002] Nylon molecular chains contain amide groups, which make it have higher heat resistance, better mechanical properties (for example, high strength, high stiffness, high wear resistance), chemical resistance, low cost and easy processing compared with other engineering plastics. It has an irreplaceable position in many fields such as automobiles, electronics, and aerospace industries. It is estimated that the global annual production of nylon will reach 10.4 million tons in 2027. Due to its long aliphatic carbon chain, nylon 66 has the characteristics of high mechanical strength and high hardness and is widely used in mechanical accessories, automobile engine blades or machine casings instead of non-ferrous metal materials. Therefore, a large amount of waste nylon 66 is generated every year by material processing and the maintenance and scrapping of automobiles, machinery, home appliances and daily necessities. Due to its non-biodegradability, the growth of nylon consumption has brought about a series of serious land and marine pollution problems. Therefore, it is of great significance to develop efficient and sustainable recycling technologies. The recycling of nylon in my country is still in its infancy, with few recycling methods and low yields. The treatment methods for waste nylon include incineration, physical recovery and chemical recovery.
[0003] During the incineration process, the oxygen and nitrogen elements in nylon will inevitably be released into the air in large quantities in the form of nitrogen oxides, causing secondary pollution to the environment. The quality and performance of the recycled materials produced by the physical recycling method are damaged, and the application field is limited. The chemical recycling method mainly uses acid-base or microwave-assisted hydrolysis or aminolysis, alcoholysis, depolymerization reactions in ionic liquids to convert nylon into monomers or oligomers. Zhou et al. used sulfuric acid to hydrolyze waste nylon 66 and converted the degradation products into bacterial cellulose (Jiangang Zhou, Yihui Chen, Yanbo Zhang, Su Sun, Muhammad WajidUllah, Weilin Xu. Biotransformation of nylon-6,6hydrolysate to bacterialcellulose. Green Chemistry 2021, 23, 7805); however, its conversion conditions are strict, the process is cumbersome, and the production cycle is as long as 17 days. Eimontas et al. used molecular sieves as catalysts to catalyze the degradation of waste nylon at 500-900°C to produce aromatic and aliphatic hydrocarbons (J. Eimontas, N. Striūgas, K. Zakarauskas, I. Catalytical thermal conversion of waste fishing nets for a higher added value energy products generation and caprolactam recovery. Fuel 2023, 334, 126735); however, the product is a mixture, the added value is not high, and the reaction conditions are harsh and the energy consumption is high.
[0004] MOF is a type of crystalline material with a regular three-dimensional network structure composed of metal ions (clusters) and organic ligands. Its structure can be regulated by selecting different metal ions and organic ligands, so that the pore structure and surface function can be precisely designed. MOF has the characteristics of highly adjustable pore structure, high specific surface area, and rich active sites. In recent years, it has been gaining popularity in the fields of gas-liquid adsorption separation, catalysis, drug delivery, optoelectronic devices, and sensor detection. Converting waste polymers into high-value-added MOF materials is a new way to recycle polymers. At present, the waste polymers reported for preparing MOF include polyethylene terephthalate, polylactic acid and polyimide (ZL 202211401069.6; ZL 202211401078.5; ZL 202310475998.X; CN202311004141.6), but due to the relatively high crystallinity, good chemical stability and high processing difficulty of polyamide, the preparation of high value-added MOF materials using waste nylon as raw materials has not been reported. In addition, there are few types of MOFs with aliphatic carboxylates as ligands in the prior art, and almost all of them are synthesized in organic solutions. If the synthesis of MOFs with aliphatic carboxylates as ligands can be achieved in water, it will undoubtedly greatly promote the large-scale production and use of MOFs with aliphatic carboxylates as ligands. Summary of the invention
[0005] In view of the above defects or improvement needs of the prior art, the purpose of the present invention is to provide a method for preparing metal-organic framework materials by degrading waste nylon 66, wherein the overall process design of the method is improved, nylon 66 is first hydrolyzed by a hydrothermal reaction in the presence of a strong base compound, and then the degradation liquid is directly used to react with a metal salt solution by a simple stirring method to synthesize MOF materials, and by controlling the temperature and time of the hydrothermal reaction and the stirring time of the stirring reaction, the waste nylon 66 is successfully degraded and the MOF material is prepared. The method of the present invention not only provides a new method for converting waste nylon 66 into high-value-added MOF materials, but also provides a new low-cost strategy for the synthesis of MOF materials.
[0006] To achieve the above object, according to the present invention, a method for preparing MOF material by degrading waste nylon 66 is provided, characterized in that it comprises the following steps:
[0007] (1) dispersing waste nylon 66 and a strong base compound in water to obtain a dispersion;
[0008] (2) subjecting the dispersion obtained in step (1) to a hydrothermal reaction at 180 to 220° C. for 12 to 36 hours to hydrolyze nylon 66 to obtain a nylon 66 degradation liquid;
[0009] (3) The nylon 66 degradation liquid obtained in step (2) is mixed with a metal salt solution and stirred at 20 to 90° C. for 10 to 30 hours to obtain a product, namely a MOF material; wherein the metal element in the MOF material is the same as the metal element in the metal salt solution.
[0010] As a further preference of the present invention, in step (1), the strong base compound is an alkali metal hydroxide, preferably at least one of sodium hydroxide and potassium hydroxide.
[0011] As a further preferred embodiment of the present invention, in step (1), the mass ratio of the strong base compound to the waste nylon 66 is 0.17-0.4:1.
[0012] As a further preferred embodiment of the present invention, in step (3), the metal salt in the metal salt solution is at least one of aluminum sulfate, silver nitrate, cobalt nitrate, copper nitrate, europium chloride, and lanthanum nitrate.
[0013] As a further preferred embodiment of the present invention, the ratio of the metal salt contained in the metal salt solution in step (3) to the waste nylon 66 in step (1) satisfies a mass ratio of 0.6 to 2.53:1.
[0014] Through the above technical scheme conceived by the present invention, compared with the prior art, the method of degrading nylon 66 and preparing high value-added MOF materials in the present invention is specifically to first hydrolyze nylon 66 in the presence of a strong base compound through a hydrothermal reaction to obtain a nylon 66 degradation liquid composed of adipate and hexamethylenediamine, and then directly use the degradation liquid to react with a metal salt solution through a simple stirring method (especially a normal temperature stirring method) to synthesize MOF materials. The strong base compound provides hydroxyl ions to react with amide bonds to generate hexamethylenediamine and adipate. Adipate has good water solubility, and the aqueous solution can provide a better reaction environment. At the same time, the adipate radical in the form of ions is more likely to coordinate with the metal ions in the metal salt solution to form a complex. Hexamethylenediamine participates in the process of forming MOF in the presence of the metal complex, and reacts with the metal ions and organic ligands in the metal complex to form a variety of coordination bonds, thereby constructing MOF. As illustrated in the examples below, based on the method of the present invention, a variety of metal ions can be selected to carry out coordination reactions with monomers in nylon 66 degradation solution, and a variety of MOF materials with different morphologies and properties can be obtained by efficient degradation reactions and simple stirring coordination reactions.
[0015] Specifically, the present invention can achieve the following beneficial effects:
[0016] (1) Compared with the traditional chemical recycling method, such as high-temperature degradation of waste nylon 66 to prepare bacterial cellulose, aromatic hydrocarbons and aliphatic hydrocarbons, the present invention realizes the degradation of waste nylon 66 to prepare MOF materials, with efficient reaction, simple steps, no need for tedious steps such as purification of nylon 66 degradation products, easy to scale up, and high added value of the product. The method of the present invention can be divided into a hydrothermal degradation stage of waste nylon 66 (this is the first stage) and a stirring reaction with metal ions to generate MOF (this is the second stage). The two stages have efficient reactions and a total duration of 1 to 4 days.
[0017] (2) Compared with the traditional method of preparing MOF, the present invention uses waste nylon 66 as a precursor of organic ligand to prepare MOF materials. The raw materials used in the preparation of MOF materials in the prior art are often small molecules with high costs; however, the present invention uses waste polymers, which has low raw material costs and can turn waste into treasure. The adipic acid ions present in the form of ions in the waste nylon 66 degradation liquid are easy to coordinate with the metal ions in the metal salt solution to form a complex. Hexamethylenediamine participates in the process of forming MOF in the presence of the metal complex, and reacts with the metal ions and organic ligands in the metal complex to form a variety of coordination bonds, thereby generating MOF. The present invention provides a new method for the low-cost preparation of MOF. In addition, the MOF obtained in the present invention is an aliphatic carboxylic acid ligand MOF. Compared with the more common MOF in the prior art that uses aromatic carboxylates such as terephthalic acid and 1,3,5-benzenetricarboxylic acid as ligands (i.e., aromatic carboxylic acid ligand MOF), the MOF that uses aliphatic carboxylic acids as ligands has higher flexibility, which gives it a unique breathing effect. In addition, the unique properties of high hydrophobicity, low optical absorption, gas adsorption selectivity and thermal stability make it have unique potential in the fields of photochemistry, photocatalysis, adsorption diffusion, and environmental monitoring.
[0018] (3) The hydrothermal degradation stage of waste nylon 66 (this is the first stage) and the stirring reaction with metal ions to generate MOF (this is the second stage) in the method of the present invention have a key impact on the final synthesis of the MOF product. Among them, the hydrothermal degradation of waste nylon 66 is carried out at 180-220°C for 12-36 hours in the presence of a strong base compound to avoid insufficient degradation of nylon 66 (when nylon 66 is not fully degraded, the MOF product and nylon 66 are both precipitated after the two-step reaction and cannot be purified and separated). The stirring reaction with metal ions is stirred at 20-90°C (such as room temperature) for 10-30 hours, which can avoid the stirring reaction time being too short, which is not conducive to the improvement of the crystallinity of the product MOF material, or the stirring reaction time being too long, which easily causes MOF to hydrolyze and fails to obtain the target MOF product; the stirring reaction in the present invention can be carried out at room temperature, and a lower temperature is not only conducive to reducing energy consumption, but also conducive to maintaining the stability of the MOF structure.
[0019] In the prior art, there has been no report on MOF using nylon as a precursor, and there are very few types of MOF using aliphatic carboxylates as ligands, and almost all of them are synthesized in organic solutions. The present invention uses waste nylon 66 as a raw material, and the MOF synthesis method is carried out in water with stirring at 20 to 90°C, with low temperature requirements.
[0020] In summary, the present invention uses a method for preparing MOF materials by degradation of nylon 66, and proposes a new chemical recycling process for nylon 66. The method of the present invention uses a hydrothermal reaction and a stirring method (especially a stirring method at room temperature) to synthesize MOF. The method is simple to operate, requires simple equipment, and has low cost. The production cycle can be as short as 1 to 4 days. It is expected to solve the problem of recycling and reusing a large amount of industrial waste nylon while producing high value-added MOF products, which is in line with the green, low-carbon, and sustainable development goals. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The X-ray powder diffraction spectrum, scanning electron microscope image, nitrogen adsorption-desorption curve and pore size distribution diagram of the Al-MOF material prepared in Example 1 are shown in FIG. Figure 1 a in the equation corresponds to the X-ray powder diffraction spectrum. Figure 1 b in the figure corresponds to the scanning electron microscope image. Figure 1 The c in the figure corresponds to the nitrogen adsorption-desorption curve. Figure 1 The d in the figure corresponds to the pore size distribution diagram.
[0022] Figure 2 The X-ray powder diffraction spectrum, scanning electron microscope image, nitrogen adsorption-desorption curve and pore size distribution diagram of the Co-MOF material prepared in Example 2. Figure 2 a in the equation corresponds to the X-ray powder diffraction spectrum. Figure 2 b in the figure corresponds to the scanning electron microscope image. Figure 2 The c in the figure corresponds to the nitrogen adsorption-desorption curve. Figure 2 The d in the figure corresponds to the pore size distribution diagram.
[0023] Figure 3 These are the X-ray powder diffraction spectrum and scanning electron microscope image of the Co-MOF material prepared in Example 3.
[0024] in, Figure 3 a in the equation corresponds to the X-ray powder diffraction spectrum. Figure 3 b in FIG. 1 corresponds to a scanning electron micrograph.
[0025] Figure 4 The X-ray powder diffraction spectrum, scanning electron microscope image, nitrogen adsorption-desorption curve and pore size distribution diagram of the Cu-MOF material prepared in Example 4 are shown in FIG. Figure 4 a in the equation corresponds to the X-ray powder diffraction spectrum. Figure 4 b in the figure corresponds to the scanning electron microscope image. Figure 4 The c in the figure corresponds to the nitrogen adsorption-desorption curve. Figure 4 The d in the figure corresponds to the pore size distribution diagram.
[0026] Figure 5The X-ray powder diffraction spectrum, scanning electron microscope image, nitrogen adsorption-desorption curve and pore size distribution diagram of the Ag-MOF material prepared in Example 5 are shown in FIG. Figure 5 a in the equation corresponds to the X-ray powder diffraction spectrum. Figure 5 b in the figure corresponds to the scanning electron microscope image. Figure 5 The c in the figure corresponds to the nitrogen adsorption-desorption curve. Figure 5 The d in the figure corresponds to the pore size distribution diagram.
[0027] Figure 6 The X-ray powder diffraction spectrum, scanning electron microscope image, nitrogen adsorption-desorption curve and pore size distribution diagram of the Eu-MOF material prepared in Example 6 are shown in FIG. Figure 6 a in the equation corresponds to the X-ray powder diffraction spectrum. Figure 6 b in the figure corresponds to the scanning electron microscope image. Figure 6 The c in the figure corresponds to the nitrogen adsorption-desorption curve. Figure 6 The d in the figure corresponds to the pore size distribution diagram.
[0028] Figure 7 The X-ray powder diffraction spectrum, scanning electron microscope image, nitrogen adsorption-desorption curve and pore size distribution diagram of the La-MOF material prepared in Example 7 are shown in FIG. Figure 7 a in the equation corresponds to the X-ray powder diffraction spectrum. Figure 7 b in the figure corresponds to the scanning electron microscope image. Figure 7 The c in the figure corresponds to the nitrogen adsorption-desorption curve. Figure 7 The d in the figure corresponds to the pore size distribution diagram.
[0029] Figure 8 X-ray powder diffraction spectrum and scanning electron microscope image of the Cu-MOF material prepared in Example 8.
[0030] in, Figure 8 a in the equation corresponds to the X-ray powder diffraction spectrum. Figure 8 b in FIG. 1 corresponds to a scanning electron micrograph.
[0031] Fig. 9 This is the X-ray powder diffraction spectrum of the material prepared in Comparative Example 2.
[0032] Fig.10 This is the X-ray powder diffraction spectrum of the material prepared in Comparative Example 3. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0034] In summary, the method for preparing a metal-organic framework material by degrading waste nylon 66 in the present invention is to first add nylon 66 and a strong base compound into a reactor, add water to dissolve the strong base compound, and react at 180-220° C. for 12-36 hours to hydrolyze nylon 66 to obtain a nylon 66 degradation liquid; then, the nylon 66 degradation liquid is mixed with a metal salt solution, stirred at 20-90° C. for 10-30 hours, and the product is washed and dried to obtain a MOF material.
[0035] The following are specific embodiments:
[0036] Example 1
[0037] Weigh 3.0g of waste nylon 66 and 0.5g of sodium hydroxide into a high-pressure reactor, add 60mL of deionized water, stir evenly to obtain a reaction dispersion, then seal the high-pressure reactor and put it into an oven, heat it at 200°C for 18h to obtain a nylon 66 degradation solution (nylon is completely degraded, and there is no precipitation in the product). Then weigh 7.6g of aluminum sulfate 18hydrate and dissolve it in 60mL of deionized water to obtain a metal salt solution. The nylon 66 degradation solution and the metal salt solution are mixed and stirred at 20°C for 10h. Finally, the product is washed and dried to obtain Al-MOF material with a yield of 99%.
[0038] Figure 1 a in the figure is the X-ray powder diffraction spectrum of Al-MOF material. Figure 1 b is a scanning electron microscope image of Al-MOF material. Figure 1 c in the figure is the nitrogen adsorption-desorption curve of Al-MOF. Figure 1 The d in the figure is the pore size distribution of Al-MOF. From the X-ray powder diffraction spectrum, it can be seen that the Al-MOF material has a characteristic diffraction peak at 5° to 10°, indicating the successful synthesis of Al-MOF. From the scanning electron microscope image, it can be seen that the morphology of the Al-MOF material is stacked nano-microspheres with a diameter of 75 to 150 nm and a specific surface area of 51 m 2 / g, and the pore structure is mostly composed of micropores less than 2nm.
[0039] Example 2
[0040] 3.0g of waste nylon 66 and 1.0g of sodium hydroxide were weighed and added to a high-pressure reactor, and 60mL of deionized water was added and stirred to obtain a reaction dispersion. The high-pressure reactor was then sealed and placed in an oven and heated at 200°C for 24h to obtain a nylon 66 degradation solution (nylon was completely degraded and there was no precipitation in the product). Then 3.4g of cobalt nitrate hexahydrate was weighed and dissolved in 60mL of deionized water to obtain a metal salt solution. The nylon 66 degradation solution and the metal salt solution were mixed and stirred at 40°C for 24h. Finally, the product was washed and dried to obtain a Co-MOF material with a yield of 98%.
[0041] Figure 2 a in the figure is the X-ray powder diffraction spectrum of Co-MOF material. Figure 2 b is a scanning electron microscope image of Co-MOF material. Figure 2 c in the figure is the nitrogen adsorption-desorption curve of Co-MOF. Figure 2 The d in the figure is the pore size distribution of Co-MOF. From the X-ray powder diffraction spectrum, it can be seen that the Co-MOF material has a characteristic diffraction peak at 5° to 10°, indicating the successful synthesis of Co-MOF. From the scanning electron microscope image, it can be seen that its surface contains a large number of nanosheets with a specific surface area of 106m 2 / g, and the pore structure is mostly mesopores with 20 to 50 nm.
[0042] Example 3
[0043] Weigh 2.5g of waste nylon 66 and 0.5g of sodium hydroxide into a high-pressure reactor, add 60mL of deionized water, stir evenly to obtain a reaction dispersion, then seal the high-pressure reactor and put it into an oven, heat it at 220°C for 15h to obtain a nylon 66 degradation solution (nylon is completely degraded, and there is no precipitation in the product). Then weigh 3.0g of cobalt nitrate hexahydrate and dissolve it in 60mL of deionized water to obtain a metal salt solution. The nylon 66 degradation solution and the metal salt solution are mixed and stirred at 25°C for 24h. Finally, the product is washed and dried to obtain Co-MOF material with a yield of 94%.
[0044] Figure 3 a in the figure is the X-ray powder diffraction spectrum of Co-MOF material. Figure 3 b is a scanning electron microscope image of the Co-MOF material. From the X-ray powder diffraction spectrum, it can be seen that the Co-MOF material has a characteristic diffraction peak at 5° to 10°, indicating the successful synthesis of Co-MOF, but its diffraction peak is not as obvious as that of the Co-MOF in Example 2, and the peak intensity of the characteristic diffraction peak at 5° to 10° is slightly weaker. From the scanning electron microscope image, it can be seen that the Co-MOF material is a stacked nanosheet with a size of 100 to 200 nm.
[0045] Example 4
[0046] 3.0g of waste nylon 66 and 1.0g of potassium hydroxide were weighed and added to a high-pressure reactor, and 60mL of deionized water was added and stirred to obtain a reaction dispersion. The high-pressure reactor was then sealed and placed in an oven and heated at 200°C for 24h to obtain a nylon 66 degradation solution (nylon was completely degraded and there was no precipitation in the product). Then 3.0g of copper nitrate trihydrate was weighed and dissolved in 60mL of deionized water to obtain a metal salt solution. The nylon 66 degradation solution and the metal salt solution were mixed and stirred at 25°C for 18h. Finally, the product was washed and dried to obtain a Cu-MOF material with a yield of 95%.
[0047] Figure 4 a in the figure is the X-ray powder diffraction spectrum of Cu-MOF material. Figure 4 b is a scanning electron microscope image of Cu-MOF material. Figure 4 c in the figure is the nitrogen adsorption-desorption curve of Cu-MOF. Figure 4 The d in the figure is the pore size distribution of Cu-MOF. From the X-ray powder diffraction spectrum, it can be seen that the Cu-MOF material has obvious characteristic diffraction peaks, indicating the successful synthesis of Cu-MOF. From the scanning electron microscope image, it can be seen that the morphology of the Cu-MOF material is stacked nanorods with a length of 1000 to 1500 nm and a specific surface area of 113 m 2 / g, and the pore structure is mostly composed of mesopores of 2 to 50 nm.
[0048] Example 5
[0049] Weigh 4.0g of waste nylon 66 and 1.3g of sodium hydroxide into a high-pressure reactor, add 60mL of deionized water, stir evenly to obtain a reaction dispersion, then seal the high-pressure reactor and put it into an oven, heat it at 180°C for 36h to obtain a nylon 66 degradation solution (nylon is completely degraded, and there is no precipitation in the product). Then weigh 2.4g of silver nitrate and dissolve it in 60mL of deionized water to obtain a metal salt solution. After mixing the nylon 66 degradation solution with the metal salt solution, stir at 90°C for 15h, and finally wash and dry the product to obtain Ag-MOF material with a yield of 76%.
[0050] Figure 5 a in the figure is the X-ray powder diffraction spectrum of Ag-MOF material. Figure 5 b is a scanning electron microscope image of Ag-MOF material. Figure 5 c in the figure is the nitrogen adsorption-desorption curve of Ag-MOF. Figure 5 The d in the figure is the pore size distribution of Ag-MOF. From the X-ray powder diffraction spectrum, we can see that the Ag-MOF material has obvious characteristic diffraction peaks, indicating the successful synthesis of Ag-MOF. From the scanning electron microscope image, we can see that the morphology of the Ag-MOF material is stacked spheres of 150 to 250 nm, with a specific surface area of 40 m2 / g, and the pore structure is mostly composed of micropores and mesopores of 3 to 50 nm.
[0051] Example 6
[0052] 3.5g of waste nylon 66 and 1.0g of sodium hydroxide were weighed and added to a high-pressure reactor, and 60mL of deionized water was added and stirred to obtain a reaction dispersion. The high-pressure reactor was then sealed and placed in an oven and heated at 180°C for 24h to obtain a nylon 66 degradation solution (nylon was completely degraded and there was no precipitation in the product). Then 2.8g of europium chloride hexahydrate was weighed and dissolved in 60mL of deionized water to obtain a metal salt solution. The nylon 66 degradation solution and the metal salt solution were mixed and stirred at 50°C for 18h. Finally, the product was washed and dried to obtain Eu-MOF material with a yield of 84%.
[0053] Figure 6 a in the figure is the X-ray powder diffraction spectrum of Eu-MOF material. Figure 6 b is a scanning electron microscope image of Eu-MOF material. Figure 6 c in the figure is the nitrogen adsorption-desorption curve of Eu-MOF. Figure 6 The d in the figure is the pore size distribution diagram of Eu-MOF. From the X-ray powder diffraction spectrum, it can be seen that the Eu-MOF material has obvious characteristic diffraction peaks, indicating the successful synthesis of Eu-MOF. From the scanning electron microscope image, it can be seen that the morphology of the Eu-MOF material is a stacked sphere of 30 to 100 nm, with a specific surface area of 70 m 2 / g, and the pore structure is mostly composed of mesopores of 2 to 3 nm.
[0054] Example 7
[0055] 3.5g of waste nylon 66 and 1.4g of potassium hydroxide were weighed and added to a high-pressure reactor, and 60mL of deionized water was added and stirred to obtain a reaction dispersion. The high-pressure reactor was then sealed and placed in an oven and heated at 220°C for 18h to obtain a nylon 66 degradation solution (nylon was completely degraded and there was no precipitation in the product). Then 3.2g of lanthanum nitrate hexahydrate was weighed and dissolved in 60mL of deionized water to obtain a metal salt solution. The nylon 66 degradation solution and the metal salt solution were mixed and stirred at 60°C for 24h. Finally, the product was washed and dried to obtain a La-MOF material with a yield of 94%.
[0056] Figure 7 a in the figure is the X-ray powder diffraction spectrum of La-MOF material. Figure 7 b is a scanning electron microscope image of La-MOF material. Figure 7 c in the figure is the nitrogen adsorption-desorption curve of La-MOF. Figure 7The d in the figure is the pore size distribution of La-MOF. From the X-ray powder diffraction spectrum, it can be seen that the La-MOF material has obvious characteristic diffraction peaks, indicating the successful synthesis of La-MOF. From the scanning electron microscope image, it can be seen that the morphology of the La-MOF material is stacked nanorods of 100 to 200 nm, with a specific surface area of 91 m 2 / g, and the pore structure is mostly mesopores of 2 to 30 nm.
[0057] Example 8
[0058] Weigh 2.5g of waste nylon 66 and 1.0g of potassium hydroxide into a high-pressure reactor, add 60mL of deionized water, stir evenly to obtain a reaction dispersion, then seal the high-pressure reactor and put it into an oven, heat it at 200°C for 30h to obtain a nylon 66 degradation solution (nylon is completely degraded, and there is no precipitation in the product). Then weigh 3.0g of copper nitrate trihydrate and dissolve it in 60mL of deionized water to obtain a metal salt solution. The nylon 66 degradation solution and the metal salt solution are mixed and stirred at 30°C for 10h. Finally, the product is washed and dried to obtain a Cu-MOF material with a yield of 95%.
[0059] Figure 8 a in the figure is the X-ray powder diffraction spectrum of Cu-MOF material. Figure 8 b is a scanning electron microscope image of the Cu-MOF material. From the X-ray powder diffraction spectrum, it can be seen that the Cu-MOF material has obvious characteristic diffraction peaks, indicating the successful synthesis of Cu-MOF. From the scanning electron microscope image, it can be seen that the morphology of the Cu-MOF material is stacked nanorods with a length of 800 to 1000 nm.
[0060] Of course, the crystallinity of the MOF product is not as good as that of the product in Example 4.
[0061] Comparative Example 1
[0062] 3.0g of waste nylon 66 and 0.5g of sodium hydroxide were weighed and added to a high-pressure reactor, and 60mL of deionized water was added and stirred evenly to obtain a reaction dispersion. The high-pressure reactor was sealed and placed in an oven, and heated at 160°C for 12h to obtain a nylon 66 degradation liquid. It was found that there was still a large amount of granular solid precipitation at the bottom of the obtained degradation liquid, and no precipitation was produced when the supernatant was added to each group of metal salt solutions, indicating that the degradation effect of nylon 66 was very poor and no MOF was generated.
[0063] Comparative Example 2
[0064] The stirring time in the above Example 2 was changed to 40 h, and the other steps remained unchanged. The obtained product changed from green to yellow, and its X-ray powder diffraction spectrum was as follows: Fig. 9 As shown, the analysis showed that it was Co(OH) 2, indicating that too long stirring time will lead to MOF hydrolysis, which is not conducive to MOF synthesis.
[0065] Comparative Example 3
[0066] The stirring time in the above Example 4 was changed to 8 h, and the other steps remained unchanged. The X-ray powder diffraction spectrum of the product is as follows Fig.10 As shown, there is no obvious diffraction peak, indicating that MOF cannot be synthesized when the stirring time is too short.
[0067] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing MOF material by degrading waste nylon 66, characterized in that: The steps include: (1) dispersing waste nylon 66 and a strong base compound in water to obtain a dispersion; (2) subjecting the dispersion obtained in step (1) to a hydrothermal reaction at 180 to 220° C. for 12 to 36 hours to hydrolyze nylon 66 to obtain a nylon 66 degradation liquid; (3) The nylon 66 degradation liquid obtained in step (2) is mixed with a metal salt solution and stirred at 20 to 90° C. for 10 to 30 hours to obtain a product, namely a MOF material; wherein the metal element in the MOF material is the same as the metal element in the metal salt solution.
2. The method according to claim 1, characterized in that: In step (1), the strong base compound is an alkali metal hydroxide, preferably at least one of sodium hydroxide and potassium hydroxide.
3. The method according to claim 1, characterized in that: In step (1), the mass ratio of the strong base compound to the waste nylon 66 is 0.17-0.4:
1.
4. The method according to claim 1, characterized in that: In step (3), the metal salt in the metal salt solution is at least one of aluminum sulfate, silver nitrate, cobalt nitrate, copper nitrate, europium chloride, and lanthanum nitrate.
5. The method according to claim 1, characterized in that: The ratio of the metal salt contained in the metal salt solution in step (3) to the waste nylon 66 in step (1) satisfies a mass ratio of 0.6 to 2.53:1.
Citation Information
Patent Citations
Mechano-chemical method for preparing metal-organic framework material
CN115678030A
Method for preparing metal-organic framework material through ball milling-solution blending
CN115716918A
Method for converting waste polylactic acid into metal-organic framework material by utilizing solvothermal
CN116425992A
Method for preparing metal-organic framework material from waste polylactic acid
CN116515125A
Method for preparing metal-organic framework by degrading polyimide through solvothermal
CN117229515A
